Existence of (∅^α⊗ψ^α ) bounded solutions of Kronecker product first order system of Differential equations (International Journal of Engineering and Computer Science, 2020)
In this paper we shall be concerned with the existence of fuzzy bounded solutions of first order Kronecker product system involving two first order fuzzy differential equations of different orders.  We show that kronecker product system is stable and asymptotically stable, if one of fuzzy systems is stable and asymptotically stable.